BUSINESS ANALYSIS FISH MAS AT POOL OF WATER POURING DOWN IN THE VILLAGE BALAI GADANG SUB-DISTRICT KOTO TANGAH PADANG CITY WEST SUMATRA PROVINCE - Fhadlon Basharahil; Hendrik '; M. Ramli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThese Research about business analysis fish mas at pool of water pouring down , which was held in August 2014 in the village Balai Gadang district Koto Tangah Padang City West Sumatra Province. The objective analyzes the cost of investment that required pool of water pouring down, the income to pool of water pouring down and fit into pool of water pouring down in the village held Big if observed from the criteria for investment. The method is used methods case studies are limited to the population, place, and a certain period of time in the field with respondents are pembudidaya fish mas pool of water pouring down that are in the village held Big namely%1 who has 12 units pool of water pouring down and 2 workers.Results of these studies indicate that the investment into fish mas pool of water pouring down of Rp1,010,619,000. Business investment Criteria fish mas pool of water pouring down an NPV of Rp 836,783,477,- BCR of 1.18 IRR of 43.75 percent and Government Regulation of 1.25.Key words: pool of water pouring down, proper business, Investment